Analysis and comparison of the bacterial σ54 regulon: Evidence of phylogenetic trends in gene regulation. - Maricela Carrera-Reyna; Edna Cruz-Flores; Enrique Merino (PLoS ONE)
While the role of σ54 in regulating genes involved in nitrogen metabolism, flagellar biosynthesis, and stress responses in Pseudomonadota is well established, its involvement in regulating alternative metabolic pathways and cellular processes in other phyla has been less explored. By employing position-specific scoring matrices (PSSMs) to identify promoter sequences regulated by the σ54 factor, we successfully predicted genes under its control across 33 taxonomic classes spanning 16 distinct phyla. For the first time, we conducted a comprehensive statistical assessment of σ54 regulation across major bacterial phylogenetic groups. Our findings provide an extensive perspective on the regulatory role of σ54 beyond nitrogen metabolism and reveal the different trends in which metabolic and biological processes can be regulated by this sigma factor depending on the phylogenetic group. The main findings of our study are available on the aRpoNDB webpage (https://biocomputo.ibt.unam.mx/arpondb/).